2021
DOI: 10.1021/acssynbio.1c00395
|View full text |Cite
|
Sign up to set email alerts
|

A Protein-Engineered, Enhanced Yeast Display Platform for Rapid Evolution of Challenging Targets

Abstract: Here, we enhanced the popular yeast display method by multiple rounds of DNA and protein engineering. We introduced surface exposure-tailored reporters, eUnaG2 and DnbALFA, creating a new platform of C and N terminal fusion vectors. The optimization of eUnaG2 resulted in five times brighter fluorescence and 10 °C increased thermostability than UnaG. The optimized DnbALFA has 10-fold the level of expression of the starting protein. Following this, different plasmids were developed to create a complex platform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…These results suggest that the mutations detected in BA.2-related Omicron variants do not affect TMPRSS2 usage. Yeast surface display assay using SARS-CoV-2 S RBD and soluble human ACE2 (Dejnirattisai et al ., 2022; Kimura et al ., 2022a; Kimura et al, 2022b; Motozono et al ., 2021; Yamasoba et al ., 2022a; Zahradnik et al, 2021a) showed that the K D value of BA.2 S RBD bearing L452R mutation is significantly lower than that of original BA.2 S RBD ( Figure 3B ), suggesting that the L452R mutation increases the binding affinity of BA.2 S RBD to human ACE2. On the other hand, the binding affinity of BA.4/5 S RBD to human ACE2 was comparable to that of BA.2 S RBD ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These results suggest that the mutations detected in BA.2-related Omicron variants do not affect TMPRSS2 usage. Yeast surface display assay using SARS-CoV-2 S RBD and soluble human ACE2 (Dejnirattisai et al ., 2022; Kimura et al ., 2022a; Kimura et al, 2022b; Motozono et al ., 2021; Yamasoba et al ., 2022a; Zahradnik et al, 2021a) showed that the K D value of BA.2 S RBD bearing L452R mutation is significantly lower than that of original BA.2 S RBD ( Figure 3B ), suggesting that the L452R mutation increases the binding affinity of BA.2 S RBD to human ACE2. On the other hand, the binding affinity of BA.4/5 S RBD to human ACE2 was comparable to that of BA.2 S RBD ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 95%
“…Yeast surface display ( Figure 3B ) was performed as previously described as previously described (Dejnirattisai et al ., 2022; Kimura et al ., 2022a; Kimura et al ., 2022b; Motozono et al ., 2021; Yamasoba et al ., 2022a; Zahradnik et al ., 2021a). Briefly, yeast codon-optimized SARS-CoV-2_RBD-Omicron-BA.2 was obtained from Twist Biosciences and the mutant RBDs were PCR amplified by KAPA HiFi HotStart ReadyMix kit (Roche, Cat# KK2601) and assembled in vivo by yeast [ Saccharomyces cerevisiae strain EBY100 (ATCC, MYA-4941)] homologous recombination with pJYDC1 plasmid (Addgene, Cat# 162458) as previously described (Dejnirattisai et al ., 2022; Kimura et al ., 2022a; Kimura et al ., 2022b; Motozono et al ., 2021; Yamasoba et al ., 2022a; Zahradnik et al ., 2021a). Primers used are listed in Table S6 .…”
Section: Star Methodsmentioning
confidence: 99%
“…Yeast surface display ( Extended Data Fig. 6b ) was performed as previously described as previously described 22, 24, 46 . Briefly, the peptidase domain of human ACE2 (residues 18-740) was expressed in Expi293 cells and purified by a 5-ml HisTrap Fast Flow column (Cytiva, Cat# 17-5255-01) and Superdex 200 16/600 (Cytiva, Cat# 28-9893-35) using an ÄKTA pure chromatography system (Cytiva), and the purified soluble ACE2 was labelled with CF640 (Biotium, Cat# 92108).…”
Section: Methodsmentioning
confidence: 99%
“…Protein production, purifications, and labeling procedures: The designed ALFA-tag binding nanobody (DnbALFA) and its mNeonGreen fusion were expressed by using expression plasmid pET28bdSUMO 62 and E.coli BL21(DE3) cells as described previously 60 . Briefly, 200 ml of 2YT medium (16 g tryptone, 10 g yeast extract and 5 g NaCl, pH 7) was inoculated (1%), grown to the OD600 = 0.6 (37°C), and the expression was initiated by the addition of IPTG to a final concentration of 0.5 mM.…”
Section: Discussionmentioning
confidence: 99%
“…The pAGDisplay vector backbone was assembled by combining a pET28b fragment bearing KanR and origin of replication, a pLVX vector fragment bearing WPRE, PuroR, and IRES sequences, and a pDisplay CMV promoter with a PDGFRβ expression cassette by a restriction-free three-component assembly 58 . In the subsequent restriction-free cloning step, the PuroR was fused with eUnaG2 fluorescent protein at the C-terminus 59,60 . The full-length pAGDisplay was sequenced to verify its correct assembly.…”
Section: Methodsmentioning
confidence: 99%